Golden Hour Protocol for Preterm Infants: A Quality Improvement Project. (December 2018) - Harriman, Tiffany L.; Carter, Brigit; Dail, Robin B.; Stowell, Katherine E.; Zukowsky, Ksenia
Abstract : Background: Preterm infants are a vulnerable patient population, especially during the first hours of life. Hypothermia, hypoglycemia, and early-onset sepsis are common problems related to prematurity. Implementation of a Golden Hour protocol has been shown to improve outcomes for preterm infants. Purpose: To evaluate the effectiveness of a Golden Hour protocol for infants born at less than 32 weeks' gestation on improving the admission process in a military care facility. Specific aims focused on temperature, time to initiation of intravenous (IV) fluids, time to administration of antibiotics, and time to close of the incubator top. Methods: A pre-/postdesign was used to compare outcomes from preimplementation to postimplementation. Predata were collected using electronic health record chart review and postdata were collected from the Neonatal Intensive Care Unit admission worksheet. Results: Although we did not find statistical significance, we found that more infants had a temperature greater than 36.5°C within 1 hour of birth and decrease in time to initiation of IV fluids and antibiotics from preimplementation to postimplementation, which is clinically significant. Time to close of the incubator top remained greater than 1 hour. Implications for Practice: Implementation of a Golden Hour protocol provides a guide to caring for preterm infants during the first hour of life to improve patient outcomes. Involvement of key stakeholders and staff education are key to successful implementation. Implications for Research: Researchers should examine long-term outcomes related to implementation of a Golden Hour protocol in future studies. Future quality improvement projects should include the effectiveness of similar protocols and address possible barriers.